2014
DOI: 10.1507/endocrj.ej14-0191
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder neuroendocrine neoplasm: a case report and critical evaluation of WHO classification

Abstract: Abstract. Gallbladder neuroendocrine neoplasms (GB-NENs) are rare. The majority of GB-NENs are poorly differentiated, with increased mitotic activity and clinically aggressive course. Surgery is the only curative approach and the optimal medical treatment is uncertain. In this report we describe the case of a woman affected by metastatic well differentiated GB-NEN with increased Ki 67. The patient underwent surgical removal of the gallbladder neoplasm and showed disease recurrence with pulmonary and liver meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
2
2
Order By: Relevance
“…7 , 13 , 28 Possible reasons include the high proportion of advanced AJCC stages (stage III: 28.6%; Stage IV: 50%), poor histological grade (100% poorly differentiated), low rate of adjuvant therapy (42.9%), and poor margin status (75% R0 resection). 29 , 30 Yan et al reported that the median survival time of NEC patients was 20.4 months, which is longer than that of this study (10.0 months). Their AJCC staging (stage III: 46.7%; stage IV: 26.7%) and histological grade (66.7% well differentiated) were relatively better than in patients in our study, which could lead to a longer survival time.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…7 , 13 , 28 Possible reasons include the high proportion of advanced AJCC stages (stage III: 28.6%; Stage IV: 50%), poor histological grade (100% poorly differentiated), low rate of adjuvant therapy (42.9%), and poor margin status (75% R0 resection). 29 , 30 Yan et al reported that the median survival time of NEC patients was 20.4 months, which is longer than that of this study (10.0 months). Their AJCC staging (stage III: 46.7%; stage IV: 26.7%) and histological grade (66.7% well differentiated) were relatively better than in patients in our study, which could lead to a longer survival time.…”
Section: Discussioncontrasting
confidence: 69%
“…The overall survival rates of NEC patients in this study were relatively lower than in previous studies 7,13,28 . Possible reasons include the high proportion of advanced AJCC stages (stage III: 28.6%; Stage IV: 50%), poor histological grade (100% poorly differentiated), low rate of adjuvant therapy (42.9%), and poor margin status (75% R0 resection) 29,30 . Yan et al reported that the median survival time of NEC patients was 20.4 months, which is longer than that of this study (10.0 months).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The exclusion criteria of the studies for literature review were as follows: (a) primary lesion arising from organs other than the gallbladder; (b) histological subtype of GB‐NET was not pathologically confirmed; (c) studies on GB‐NET or well‐differentiated MiNEN; (d) review articles, meta‐analyses, editorials, commentaries, or animal studies, etc; (e) the required clinicopathological data could not be extracted; and (f) insufficient data on the follow‐up or patient outcomes. After literature search data of additional 47 patients from 38 studies were obtained 5,7,9–44 . Finally, a total of 62 patients with GB‐NEC including poorly differentiated MiNEN were finally enrolled.…”
Section: Methodsmentioning
confidence: 99%